Comparative Transcriptome Analysis Reveals Relationship among mRNAs, lncRNAs, and circRNAs of Slow Transit Constipation. - Yan, Shuai; Yue, Yinzi; Sun, Mingming; Chen, Yinghui; Wang, Xiaopeng; Qian, Haihua (BioMed Research International, 2021)
Background. Slow transit constipation (STC) is characterized by persistent, infrequent, or incomplete defecation. Systematic analyses of mRNA, lncRNA, and circRNA expression profiling in STC provide insights to understand the molecular mechanisms of STC pathogenesis. The present study is aimed at observing the interaction of mRNAs, lncRNAs, and circRNAs by RNA sequencing in vivo of STC. Methods. A rat model of STC was induced by loperamide. The expression profiles of both mRNAs and miRNAs were performed by RNA sequencing. Enrichment analyses of anomalous expressed mRNAs, lncRNAs, and circRNAs were performed in order to identify the related biological functions and pathologic pathways through the Gene Ontology (GO) database and Kyoto Encyclopedia of Genes and Genomes (KEGG) database. Results. In total, 26435 mRNAs, 5703 lncRNAs, and 7708 circRNAs differentially expressed were identified between the two groups. The analyses of GO and KEGG show that (1) upregulated genes were enriched in a positive regulation of GTPase activity, cell migration, and protein binding and lipid binding and (2) GO annotations revealed that most trans-target mRNAs are involved in the regulation process of immune signal together with the proliferation and differentiation of immune cells. Additionally, the protein-protein interaction (PPI) network of differentially expressed (DE) mRNAs was constructed. Interestingly, all of the core lncRNAs and their coexpression mRNAs in this network are downregulated. Moreover, downregulated circRNAs have a set of target mRNAs related to immunoreaction, which was consistent with the overall tendency. Conclusion. Our investigation enriches the STC transcriptome database and provides a preliminary exploration of novel candidate genes and avenues expression profiles in vivo. The dysregulation of mRNAs, lncRNAs, and circRNAs might contribute to the pathological processes during STC.